S52 Suberanilohydroxamic acid (SAHA) inhibits collagen deposition in a transforming growth factor β1-driven precision cut lung slice (PCLS) model of pulmonary fibrosis - Brand, Oliver J.; Pasini, Alice; Habgood, Antony; Knox, Alan J.; Jenkins, Gisli; Pang, Linhua (BMJ Publishing Group, 2016)
Introduction and objectives Idiopathic Pulmonary Fibrosis (IPF) is a chronic, progressive interstitial lung disease that is refractory to current treatment options. Transforming growth factor (TGF)-β1 is a key pro-fibrotic cytokine that plays a crucial role in IPF pathogenesis. Our group previously demonstrated distinct epigenetic modifications involved in repression of the antifibrotic gene cyclooxygenase-2 (COX-2) in fibroblasts from IPF (F-IPF) lungs compared with fibroblasts from non-fibrotic lungs (F-NL). Epigenetic drugs capable of inhibiting DNA and histone modifications may, therefore, represent a putative novel therapy. The aim of this study was to investigate the ability of 4 epigenetic inhibitors to regulate TGF-β-driven fibrosis in ex vivo mouse lung.